Earthquakes - Branley, Franklyn M. (Franklyn Mansfield), 1915-2002 (Let's-read-and-find-out science., 2005)
Read and find out about one of nature's most mysterious forces-the earthquake. Some earthquakes are so small that you don't even feel them, while others can make even big buildings shake! Learn why earthquakes happen, where they are most likely to occur, and what to do if one happens near you.